PENGARUH KADAR ASAM SULFAT PADA HIDROLISIS TANDAN KOSONG KELAPA SAWIT (TKS) DAN WAKTU FERMENTASI TERHADAP KADAR BIOETANOL YANG DIHASILKAN - Sartini sartini; Rita Fitriani; Rosliana Lubis (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2018)
The effect of sulphuric acid fermentation of processed palm oil bunch hydrolysis and on ethanol and sugar production was conducted. The aim was to investigate the hydrolytic optimum required by Saccharomyces cerevisiae for ethanol and sugar production. About 12.5 g powdered palm oil bunch was used in this experiment. The powder was hydrolized several times using sulphuric acid in several concentration. Sugar, product of  hydrolysis, was detected every one hour using spectrophotometer. The sugar was fermented by Saccharomyces cerevisiae and incubated for several days. Results showed that 2-4% sulphuric acid was oprimum concentration for 30 g/L sugar production. The highest ethanol production 4.94% occurred after two days fermentation.